Individual variation in undergraduate student metacognitive monitoring and error detection during biology model evaluation - Dauer, Joseph; Behrendt, Mei Grace; Elliott, McKenna; Gettings, Bethany; Long, Tammy; Clark, Caron (Frontiers in Education, 2024)
Models are a primary mode of science communication and preparing university students to evaluate models will allow students to better construct models and predict phenomena. Model evaluation relies on students' subject-specific knowledge, perception of model characteristics, and confidence in their knowledge structures. Fifty first-year college biology students evaluated models of concepts from varying biology subject areas with and without intentionally introduced errors. Students responded with 'error' or 'no error' and 'confident' or 'not confident' in their response. Overall, students accurately evaluated 65% of models and were confident in 67% of their responses. Students were more likely to respond accurately when models were drawn or schematic (as opposed to a boxand-arrow format), when models had no intentional errors, and when they expressed confidence. Subject area did not affect the accuracy of responses. Variation in response patterns to specific models reflects variation in model evaluation abilities and suggests ways that pedagogy can support student metacognitive monitoring during model-based reasoning. Error detection is a necessary step towards modeling competence that will facilitate student evaluation of scientific models and support their transition from novice to expert scientists.